The effect of number of vacuum thermal evaporation cycles to the optoelectronic and morphological properties of ZnO - Azmi, Fatin Farisha Alia; Muzakir, Saifful K.; Kadir, Mohd Fakhrul Zamani; Aziz, Shujahadeen B. (Universiti Putra Malaysia, 2021)
Zinc oxide (ZnO) is a wide band gap material (~3.37 eV) which has small exciton Bohr radius ~2.34 nm. In dye-sensitized solar cell, ZnO thin film is used as photoelectrode. Light-sensitive organic/ inorganic fluorophores could be adsorbed on the surface of the ZnO film, which later will be sandwiched with electrolyte and a counter electrode. The aim of this paper is to study the effect of number of evaporation cycle to the yielded morphology and size of ZnO building blocks; deposited using one, two, and three cycles of vacuum thermal evaporation technique. The ZnO thin films have been deposited on ITO glass substrate at vacuum pressure of 5 ´ 10-5 Torr, 116 A, and 2.6 V. The morphology of the thin films has been examined under Field Emission Scanning Electron Microscope (FESEM), which showed nanosphere morphology. The morphological observation is supported by a simulation; which calculated based on the crystallographic properties of the synthesized ZnO – characterized by X-ray diffractometer (XRD). Three sets of the ZnO thin films consists of ZnO particles in the range of 8 – 20 nm, 11 – 37 nm, and 6 – 16 nm respectively. According to the optical properties characterized by absorption spectrometer, it has been observed that the band gap of the thin films increased with increasing number of evaporation cycles. The values of the optical bandgap, Eg evaluated from Tauc’s plot, were found in the range between 2.40 eV to 2.60 eV.